2016
DOI: 10.1039/c5ra24262b
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial tension of oil/water emulsions with mixed non-ionic surfactants: comparison between experiments and molecular simulations

Abstract: Stable oil/water emulsions are usually obtained by using mixtures of different surfactants. Such systems display synergistic interface stabilizing effects, which have not been fully elucidated yet. Moreover, in many applications surfactants are added at concentrations well above their critical micellar concentration (CMC), and this regime has not been thoroughly explored in the literature as well. Here, we investigate oil/water emulsions through oil/water interfacial tension using two common non-ionic surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 53 publications
2
48
0
Order By: Relevance
“…The ability of small‐molecule surfactants to form small oil droplets during the homogenisation process is well documented and attributed to their ability to adsorb quickly to the oil–water interface and effectively lower the interfacial tension (Piorkowski & McClements, ). The emulsifier concentration (1%) exceeds the critical micellar concentration (CMC) for Tween 80, which practically means that the interface is densely populated by surfactant molecules and the excess spontaneously self‐assembles into micelles in the continuous phase to further reduce the interfacial tension (Posocco et al ., ). The TSI of the Tween 80‐stabilised emulsions was the lowest compared with all other samples indicating that the surfactant was the most effective emulsifier to form and stabilise the emulsion beverage.…”
Section: Resultsmentioning
confidence: 97%
“…The ability of small‐molecule surfactants to form small oil droplets during the homogenisation process is well documented and attributed to their ability to adsorb quickly to the oil–water interface and effectively lower the interfacial tension (Piorkowski & McClements, ). The emulsifier concentration (1%) exceeds the critical micellar concentration (CMC) for Tween 80, which practically means that the interface is densely populated by surfactant molecules and the excess spontaneously self‐assembles into micelles in the continuous phase to further reduce the interfacial tension (Posocco et al ., ). The TSI of the Tween 80‐stabilised emulsions was the lowest compared with all other samples indicating that the surfactant was the most effective emulsifier to form and stabilise the emulsion beverage.…”
Section: Resultsmentioning
confidence: 97%
“…This category of emulsions is generally thermodynamically unstable as the two phases tend to coalesce and separate due to the reduction in interfacial energies over time. However, the stabilization mechanisms can eliminate the rate of droplet coalescence . The majority of the produced emulsions belong to this category.…”
Section: Theoretical Aspects Of Emulsionsmentioning
confidence: 99%
“…However, the stabilization mechanisms can eliminate the rate of droplet coalescence. [23] The majority of the produced emulsions belong to this category. There is a second group of emulsions, in contrast to macro-emulsions, labelled as micro-emulsions.…”
Section: Types Of Emulsionsmentioning
confidence: 99%
“…Generally, this synergistic effect produces more compact micelles with smaller size. Posocco et al [54] also revealed a significant synergistic effect between Tween-Span surfactants molecule. They showed that low molecular weight Span molecules occupied free spaces between the much larger, bulky Tween compounds.…”
Section: Wang Et Al Observed a Lattice Spacing Of 048 Nm For Fe3o4 mentioning
confidence: 97%